Subtle crossover from C-H center dot center dot center dot O to S=O center dot center dot center dot C=O short contacts in the association of diastereomers of 2,4(6)-di-O-benzoyl-6(4)-O-[(1S)-10-camphorsulfonyl]-myo-inositol 1,3,5-orthoformate upon format - Manoj, Kochunnoonny; Gonnade, Rajesh G.; Bhadbhade, Mohan M.; Shashidhar, Mysore S. (Crystal Growth & Design, 2006)
Diastereomers of 2,4(6)- di-O-benzoyl-6(4)-O-[(1S)-10-camphorsulfonyl]-myo-inositol 1,3,5-orthoformate associate via weak interactions to form ``head-to-head'' dimers in their crystals. Molecular association through C-H center dot center dot center dot O short contacts do not leave any void for the guest inclusion, while association through S=O center dot center dot center dot C=O bridging produces pseudopolymorphs. Three crystalline modifications are observed for the title compound: form I, monoclinic P2(1), without any guest solvent, and solvated forms II and III, that belong to monoclinic space groups P2(1) and C2, respectively. A majority of solvates, which include pyridine, dichloromethane, benzene, tetrahydrofuran, and cyclohexanone as guests, belong to form III. All these guests have 2-fold symmetry axes ( C2) with their electron count within 40-62 electrons; guest selectivity experiments indicate that planar aromatic guests ( pyridine, benzene) bind better to the host molecules as compared to nonplanar guests ( dioxane, cyclohexanone). The molecular packing that is created thorough channels in the crystal ( avoiding interpenetration of the layers) are of interest because of their potential application in molecular separation by forming selective inclusions. The diastereomeric association via S=O center dot center dot center dot C=O dipolar short contacts, a consistent feature observed in all the solvates, is thought to have relevance in the binding of sulfonyl drugs to the C=O moieties of the receptor proteins.

Investigating organization of molecules that facilitates intermolecular acyl transfer in crystals: reactivity and x-ray structures of O-benzoyl-myo-inositol 1,3,5-orthoesters - Murali, Chebrolu; Shashidhar, Mysore S.; Gonnade, Rajesh G.; Bhadbhade, Mohan M. (European Journal of Organic Chemsitry, 2007)
{Crystal structure analysis of racemic 2,6-di-O-benzoyl-myo-inositol 1,3,5-orthobenzoate reveals helical organization of the molecules, remarkably similar to that observed earlier in crystals of racemic 2,6-di-O-benzoyl-myo-inositol 1,3,5-orthoformate. Both these dibenzoates are isostructural despite the bulkier phenyl substituent in place of hydrogen. The latter compound shows highly facile intermolecular benzoyl transfer reactivity in its crystals and as anticipated from the crystal structure, the orthobenzoate indeed exhibits facile benzoyl transfer reactivity in its crystals. 2-O-Benzoyl-myo-inositol 1,3,5-orthoformate and the corresponding orthobenzoate also undergo transesterification in their crystals, but the specificity of acyl transfer is very low, and the reaction yields a mixture of products. The parameters of helical molecular assembly that facilitates acyl transfer in crystals have been investigated. A comparison of the molecular assemblies and lattice interactions in crystals of all the four compounds with the observed reactivity patterns show that facile acyl transfer reaction is brought about by a modular ``reaction tunnel''
Keywords: AOT; CdS-Ag2S; core-shell; Nanoparticles; w/o microemulsion; XPS

Crystal-to-crystal transformation amongst dimorphs of racemic 2,6-di-O-(p-halobenzoyl)-myo-inositol 1,3,5-orthoformates that achieves halogen bonding contacts - Gonnade, Rajesh G.; Bhadbhade, Mohan M.; Shashidhar, Mysore S. (CrystEngComm, 2008)
{Racemic 2,6-di-O-(p-halobenzoyl)-myo-inositol 1,3,5-orthoformates (bromo (1) and chloro (2)) produced two polymorphs each, thin needle type crystals (Form I) were obtained from methanol, whereas larger rectangular crystals (Form II) were produced from ethyl acetate. Both forms could be produced concomitantly on crystallization (of 1 or 2) from ethyl acetate-light petroleum ether mixture; the yield of Form II crystal was always much more compared to Form I crystals. Although, a one-dimensional isostucturality linking molecules via O-H center dot center dot center dot O hydrogen bonding is seen in both forms, the difference arises in linking these chains. In larger Form II crystals (of 1 and 2), the adhesions are via halogen bonding (C-X center dot center dot center dot O=C

Inositol derived crown ethers: effect of auxiliary protecting groups and the relative orientation of crown ether oxygen atoms on their metal ion binding ability - Dixit, Shailesh S.; Shashidhar, Mysore S. (Tetrahedron, 2008)
The binding constants of crown ethers prepared from tetra-O-substituted myo- and scyllo-inositol derivatives and 2-O-substituted myo- and scyllo-inositol-1,3,5-orthoformates, with metal picrates show that the O-substituents and the relative orientation of the crown ether oxygen atoms contribute significantly to the binding of crown ethers with metal ions. In particular, the binding efficiency of myo-inositol derived crown ethers to silver and potassium ions could be enhanced by introducing benzyl ethers in the inositol ring. Hence binding efficacy and selectivity of metal ions to inositol derived crown ethers can be tuned by varying substituents on the myo-inositol ring and/or the relative orientation of crown ether oxygen atoms. (C) 2007 Elsevier Ltd. All rights reserved.
Keywords: crown ether; Cyclitol; Inositol; ligand; metal complex; supramolecule

Enhancing intermolecular benzoyl-transfer reactivity in crystals by growing a ``reactive'' metastable polymorph by using a chiral additive - Murali, Chebrolu; Shashidhar, Mysore S.; Gonnade, Rajesh G.; Bhadbhade, Mohan M. (Chemistry-A European Journal, 2009)
Racemic 2,4-di-O-benzoyl-myo-inositol-1,3,5-orthoacetate, which normally crystallizes in a monoclinic form (form I, space group P2(1)/n) could be persuaded to crystallize out as a metastable polymorph (form II, space group C2/c) by using a small amount of either D- or L- 2,4-di-O-benzoyl-myo-inositol-1,3,5-orthoformate as an additive in the crystallization medium. The structurally similar enantiomeric additive was chosen by the scrutiny of previous experimental results on the crystallization of racemic 2,4-di-O-benzoyl-myo-inositol-1,3,5-orthoacetate. Form II crystals call be thermally transformed to form I crystals at about 145 degrees C. The relative organization of the molecules in these dimorphs vary slightly in terms of the helical assembly of molecules, that is, electrophile (El)center dot center dot center dot nucleophile (Nu) and C-H center dot center dot center dot pi interactions, but these minor variations have a profound effect on the facility and specificity of benzoyl-group-transfer reactivity in the two crystal forms. While form II crystals undergo a clean intermolecular benzoyl-group-transfer reaction, form I crystals are less reactive and undergo non-specific benzoyl-group transfer leading to a Mixture of products. The role played by the additive in fine-tuning small changes that are required in the molecular packing opens up the possibility of creating new polymorphs that show varied physical and chemical properties. Crystals of D-2.6-di-O-benzoyl-myo-inositol-1,3,5-orthoformate (additive) did not show facile benzoyl-group-transfer reactivity (in contrast to the corresponding racemic compound) due to the lack of proper juxtaposition and assembly of molecules.
Keywords: Acylation; carbohydrates; Crystal growth; cyclitols; solid-state reactions

Isostructural molecular strings linked via conserved dipolar (ether) O center dot center dot center dot C=O short contacts in conformational polymorphs of racemic 2,4-di-O-acetyl-6-O-tosyl-myo-inositol 1,3,5-orthoesters - Manoj, Kochunnoonny; Gonnade, Rajesh G.; Bhadbhade, Mohan M.; Shashidhar, Mysore S. (CrystEngComm, 2009)
Conformational dimorphs of racemic 2,4-di-O-acetyl-6-O-tosyl-myo-inositol 1,3,5-orthoformate and its orthoacetate analogue were characterized using single crystal X-ray diffraction, thermal analysis and hot-stage microscopy techniques. In these polymorphs, the tosyl group adopted different conformations due to the rotation about the O-S bond. A significant variation in the torsion angle for the tosyl group (similar to 56 degrees) was observed for Form II crystal of the orthoformate derivative, which exhibited an intramolecular dipolar S=O center dot center dot center dot C=O (sulfonyl-carbonyl) short contact. An interesting feature in all conformational polymorphs is the formation of an isostructural string (despite the differences in the orientation of the tosyl group) linked via dipolar (ether) O center dot center dot center dot C=O contacts, which is further stitched by other weak interactions to form different layers in their crystal lattice.

Regioselective O-acylation of myo-inositol 1,3,5-orthoesters: dependence of regioselectivity on the stoichiometry of the base - Sureshan, Kana M.; Devaraj, Subramanian; Shashidhar, Mysore S. (Tetrahedron, 2009)
A metal mediated unusual 1-3 acyl migration from C4-O to C2-OH of myo-inositol 1,3,5-orthoformate was observed during the alkylation of racemic 4-O-benzoyl-myo-inositol 1,3,5-orthoformate. This has been exploited for the selective esterification of either the C4(6)-OH or the C2-OH of myo-inositol by varying the amount of the base used. While the use of 1 equiv of the base (sodium hydride or potassium tert-butoxide) for the acylation of myo-inositol orthoesters gives the corresponding C4-ester exclusively, the use of two or more equivalents of base for the same reaction gives the C2-ester exclusively. The relatively higher stability of the alkoxide of racemic 2-O-acyl-myo-inositol 1,3,5-orthoester as compared to the alkoxide of 4-O-acyl-myo-inositol 1,3,5-orthoester is suggested to be responsible for the observed isomerization. (c) 2009 Elsevier Ltd. All rights reserved.
Keywords: Acylation; Cyclitol; Inositol; Orthoester; Regioselectivity; transesterification

Relative reactivity of hydroxyl groups in inositol derivatives: role of metal ion chelation - Devaraj, Subramanian; Jagdhane, Rajendra C.; Shashidhar, Mysore S. (Carbohydrate Research, 2009)
O-Alkylation of myo-inositol derivatives containing more than one hydroxyl group via their alkali metal alkoxides (sodium or lithium) preferentially occurs at a hydroxyl group having a vicinal cis-oxygen atom. In general the observed selectivity is relatively higher for lithium alkoxides than for the corresponding sodium alkoxide. The observed regioselectivity is also dependent on other factors such as the solvent and reaction temperature. A perusal of the results presented in this article as well as those available in the literature suggests that chelation of metal ions by inositol derivatives plays a significant role in the observed regioselectivity. Steric factors associated with the axial or equatorial disposition of the reacting hydroxyl groups do not contribute much to the outcome of these O-alkylation reactions. These results could serve as guidelines in planning synthetic strategies involving other carbohydrates and their derivatives. (C) 2009 Elsevier Ltd. All rights reserved.
Keywords: Carbohydrate; Chelation; Cyclitol; Inositol; Protecting group

Two modes of O-H center dot center dot center dot O hydrogen bonding utilized in dimorphs of racemic 6-O-acryloyl-2-O-benzoyl-myo-inositol 1,3,5-orthoformate - Krishnaswamy, Shobhana; Gonnade, Rajesh G.; Bhadbhade, Mohan M.; Shashidhar, Mysore S. (Acta Crystallographica Section C-Crystal Structure Communications, 2009)
The title compound, C(17)H(16)O(8), yields conformational dimorphs [forms (I) and (II)] at room temperature, separately or concomitantly, depending on the solvent of crystallization. The yield of crystals of form (I) is always much more than that of crystals of form (II). The molecule has one donor -OH group that can make intermolecular O-H center dot center dot center dot O hydrogen bonds with one of the two acceptor C O groups, as well as with the hydroxyl O atom; interestingly, each of the options is utilized separately in the dimorphs. The crystal structure of form (I) contains one molecule in the asymmetric unit and is organized as a planar sheet of centrosymmetric dimers via O H center dot center dot center dot O hydrogen bonds involving the OH group and the carbonyl O atom of the acryloyl group. In the crystal structure of form (II), which contains two independent molecules in the asymmetric unit, two different O-H center dot center dot center dot O hydrogen bonds, viz. hydroxyl-hydroxyl and hydroxyl-carbonyl (benzoyl), connect the molecules in a layered arrangement. Another notable feature is the transformation of form (II) to form (I) via melt crystallization upon heating to 411 K. The higher yield of form (I) during crystallization and the thermal transition of form (II) to form (I) suggest that the association in form (I) is more highly favoured than that in form (II), which is valuable in understanding the priorities of molecular aggregation during nucleation of various polymorphs.

Crystal-to-crystal thermal phase transition amongst dimorphs of hexa-O-p-toluoyl-myo-inositol conserving two-dimensional isostructurality - Gonnade, Rajesh G.; Bhadbhade, Mohan M.; Shashidhar, Mysore S. (Crystengcomm, 2010)
Triclinic (P-1) crystals of hexa-O-p-toluoyl-myo-inositol obtained from common organic solvents exhibited single crystal-to-single crystal irreversible phase transition centered at similar to 250 degrees C. The transformation of these crystals to monoclinic P2(1)/n form was revealed using DSC and X-ray diffraction studies. The latter crystals could also be produced by melt crystallization. Crystal structure analysis revealed that the molecules in both forms are linked via bifurcated C-H center dot center dot center dot O interactions to make almost identical centrosymmetric dimers. The neighbouring dimers are bridged via C-H center dot center dot center dot O and aromatic pi center dot center dot center dot pi stacking interactions to create two-dimensional isostructural assemblies. The difference in the two crystal forms arises from linking of the centrosymmetric dimers along the third dimension; the dimers are centrosymmetrically bridged in the triclinic form, while they have n-glide relationship in the monoclinic form. Comparison of the dimorph structures further revealed that they are actually an excellent case of morphotropism since dimorphs are related by non crystallographic rotation and translation of their basic motif (centrosymmetric dimers) that transforms the triclinic (P-1) phase to a monoclinic (P2(1)/n) phase.

Helical self-assembly of molecules in pseudopolymorphs of racemic 2,6-di-O-(4-halobenzoyl)-myo-inositol 1,3,5-orthoformates: clues for the construction of molecular assemblies for intermolecular acyl transfer reaction - Krishnaswamy, Shobhana; Gonnade, Rajesh G.; Shashidhar, Mysore S.; Bhadbhade, Mohan M. (Crystengcomm, 2010)
The crystal structure of racemic 2,6-di-O-benzoyl-myo-inositol 1,3,5-orthoformate (1) which underwent a facile intermolecular benzoyl transfer reaction in the solid state, revealed a helical assembly of molecules along the two-fold screw axis via O-H center dot center dot center dot O hydrogen bond bringing the electrophile (C=O) and the nucleophile (-OH) in close proximity along the helical axis. However, structurally related racemic 2,6-di-O-(p-halobenzoyl)-myo-inositol 1,3,5-orthoformates (bromo (2) and chloro (3)) produced triclinic dimorphs (both P (1) over bar) when crystallized from methanol and ethyl acetate. Molecules in either form did not assemble spirally (like 1), and instead exhibited a one-dimensional isostructurality, bridging O-H center dot center dot center dot O linked identical molecular strings via C-H center dot center dot center dot O interactions across the inversion center. However, the molecules of 2 and 3 assembled in a helical manner similar to 1 with inclusion of solvent molecules in the crystal lattice when crystallized from other common organic solvents. Remarkably, in all the solvates the host molecules formed strikingly similar helices around the crystallographic 2(1)-screw axis through O-H center dot center dot center dot O bond involving the -OH group and carbonyl oxygen of the equatorial C2-O-benzoyl group. Comparison of the crystal structure of dimorphs and the solvatomorphs revealed that the solvent molecules, which interact with the orthoformate-bridge, trigger the helix formation of the host. The difference in the crystal structures of solvatomorphs arises in the interlinking of the neighbouring helices, which creates voids of different sizes to accommodate the solvent molecules. All the solvates crystallized in the monoclinic system distributed over three different space groups P2(1)/n, P2(1)/c and C2/c. In the P2(1)/n system, the adjacent helices are linked via C-X center dot center dot center dot O contacts, in P2(1)/c via C-H center dot center dot center dot X (X Cl, Br) contacts and in C2/c via short X center dot center dot center dot X contacts (X = Cl). The helical organization achieved through solvent mediation and inclusion is of significance in creating molecular packing for intermolecular acyl transfer reactions in crystals.

Intramolecular hydrogen abstraction in radicals derived from inositol 1,3-acetals: efficient access to cyclitols - Murali, Chebrolu; Gurale, Bharat P.; Shashidhar, Mysore S. (European Journal of Organic Chemistry, 2010)
The benzylidene acetals obtained by cleavage of the orthobenzoate moiety in myo-mositol 1,3,5-orthobenzoate were used to prepare mono- as well as di-deoxy inositol derivatives via their xanthates. The dideoxygenation is a result of intramolecular abstraction of the benzylidene acetal hydrogen and subsequent cleavage of the acetal ring. Such a cleavage does not take place in analogous acetals derived from other orthoesters. The 1,3-acetals derived from myoinositol 1,3,5-orthoesters were also used to prepare neo-inositol and isomeric deoxy-amino inositols, Most of the reactions in these synthetic sequences starting from myo-inositol give one product in each step. The results presented here show that myo-inositol 1,3,5-orthobenzoate offers many advantages over other orthoesters for the synthesis of cyclitol derivatives from myo-inositol.
Keywords: cyclitols; Deoxygenation; Inosamine; Inositol; Radical reactions; Radicals; Xanthate

Orthogonally protected cyclohexanehexols by a ``one reaction - one product'' approach: efficient access to cyclitols and their analogs - Jagdhane, Rajendra C.; Shashidhar, Mysore S. (European Journal of Organic Chemistry, 2010)
Differentially protected myo-inositol derivatives were prepared from commercially available myo-inositol through regioselective O-alkylation reactions, which give a single product in each step. These derivatives were converted into six isomeric inositol derivatives carrying orthogonal hydroxy protecting groups. For all these reactions, conditions were chosen to prevent the formation of isomeric products, which obviates the need for separation of isomers and provides the required cyclitol derivative in very good yields. The synthetic potential of these derivatives was illustrated by the conversion of some of the orthogonally protected inositol derivatives into other cyclitol derivatives. Isomeric inositols were also prepared by the global deprotection of all the hydroxy groups.
Keywords: Alkylation; cyclitols; Inositol; Protecting groups; Regioselectivity

Comparison of racemic epi-inosose and (-)-epi-inosose - Krishnaswamy, Shobhana; Patil, Madhuri T.; Shashidhar, Mysore S. (ACTA Crystallographica Section C-Crystal Structure Communications, 2011)
The conversion of myo-inositol to epi-inositol can be achieved by the hydride reduction of an intermediate epi-inosose derived from myo-inositol. (-)-epi-Inosose, (I), crystallized in the monoclinic space group P2(1), with two independent molecules in the asymmetric unit [Hosomi et al. (2000). Acta Cryst. C56, e584-e585]. On the other hand, (2RS,3SR,5SR,6SR)epi-inosose, C6H10O6, (II), crystallized in the orthorhombic space group Pca2(1). Interestingly, the conformation of the molecules in the two structures is nearly the same, the only difference being the orientation of the C-3 and C-4 hydroxy H atoms. As a result, the molecular organization achieved mainly through strong O-H center dot center dot center dot O hydrogen bonding in the racemic and homochiral lattices is similar. The compound also follows Wallach's rule, in that the racemic crystals are denser than the optically active form.

Formal synthesis of valiolamine from myo-inositol - Jagdhane, Rajendra C.; Shashidhar, Mysore S. (Tetrahedron, 2011)
An efficient formal synthesis of racemic valiolamine starting from readily available myo-inositol is reported. In all the synthetic steps only one regioisomer is formed, which circumvents laborious purification of products. Regioselective benzylation of myo-inositol orthoformate, super-hydride mediated deoxygenation of a cyclitol derivative and stereoselective addition of dichloromethyllithium to an inosose are the key reactions in the synthesis. (C) 2011 Elsevier Ltd. All rights reserved.
Keywords: Amino sugar; Carbohydrate; Cyclitol; Inositol; Natural product; Valiolamine

Intermolecular benzoyl group transfer reactivity in crystals of racemic 2,6-di-O-benzoyl-myo-inositol 1,3,5-orthobenzoate: controlling reactivity by solvate (pseudopolymorph) formation - Krishnaswamy, Shobhana; Shashidhar, Mysore S.; Bhadbhade, Mohan M. (Crystengcomm, 2011)
Racemic 2,6-di-O-benzoyl-myo-inositol 1,3,5-orthobenzoate (rac-3), which usually crystallizes in a monoclinic lattice (Form I, P2(1)/c) from common organic solvents, when crystallized from 2-propanol yielded concomitantly, thin whisker like crystals (Form II, triclinic, P (1) over bar) with inclusion of 2-propanol and water molecules, along with the Form I crystals. Thin fibre-like crystals were also obtained on crystallization from toluene, with inclusion of toluene and water in the crystal lattice (Form III). The Form II and Form III crystals could be converted into the Form I crystals thermally via melt crystallization. Form I crystals exhibit a facile transesterification reaction, but the solvated crystals are unreactive under the same conditions until their transformation to the reactive form. The reactivity patterns of the Form I and Form II crystals correlate well with the molecular organization in them. Since reactivity of the crystals of rac-3 depends on the solvent and the method of crystallization, and the thermal transition of one crystal form to the other, these phase changes can be used as a switch to control the benzoyl transfer reactivity of the constituent molecules in crystals.

Protecting group directed stereoselective reduction of an epi-inosose: efficient synthesis of epi-inositol - Patil, Madhuri T.; Krishnaswamy, Shobhana; Sarmah, Manash P.; Shashidhar, Mysore S. (Tetrahedron Letters, 2011)
A facile and high yielding synthesis of epi-inositol via stereoselective reduction of a pentaprotected epi-inosose is reported. Extent of stereoselectivity during the hydride reduction appears to depend on the ability of the substrate to complex with metal ions in the reducing agent. (C) 2011 Elsevier Ltd. All rights reserved.
Keywords: Cyclitol; Inositol; Polyol; reduction; Stereoselective

Thermal epimerization of inositol 1,3-benzylidene acetals in the molten state - Gurale, Bharat P.; Krishnaswamy, Shobhana; Vanka, Kumar; Shashidhar, Mysore S. (Tetrahedron, 2011)
1,3-O-Benzylidene-2,4,5,6-tetra-O-substituted-myo-inositol derivatives obtained by the DIBAL-H reduction of the corresponding myo-inositol 1,3,5-orthobenzoate derivatives undergo epimerization at the acetal carbon on heating, in the molten state, just above their melting point. The same epimerization reaction does not proceed either in the crystalline state or in solution. DFT calculations suggest that the epimeric acetal obtained by this thermal process is relatively more stable than the starting acetal. Either of these acetals could not be obtained by the reaction of the corresponding inositol derived diol with benzaldehyde. These observations constitute a novel reaction solely in the molten state, which are rarely encountered in the literature. X-ray crystal structures of the epimeric acetals as well as their radical deoxygenation reaction are also reported. (C) 2011 Elsevier Ltd. All rights reserved.
Keywords: cyclitols; Deoxygenation; Epimerization; Melt; Xanthate

Achieving molecular stability of racemic 4-O-benzyl-myo-inositol-1,3,5-orthoformate through crystal formation - Sardessai, Richa; Krishnaswamy, Shobhana; Shashidhar, Mysore S. (Crystengcomm, 2012)
Molecular stability of racemic 4-O-benzyl-myo-inositol-1,3,5-orthoformate, an early intermediate during the synthesis of phosphoinositols, depends on the phase in which it is stored. This orthoformate is stable when stored in the crystalline form or as solution in common organic solvents. The former has eluded chemists since the preparation of this benzyl ether two decades ago. The difficulty in obtaining crystals of this orthoformate is due to the cleavage of the orthoformate moiety during storage in the gummy state. Dimorphs (form I and form II) of crystalline racemic 4-O-benzyl-myo-inositol-1,3,5-orthoformate, were obtained when the gummy sample was stored over extended periods of time. Form I crystals could be obtained consistently, by crystallization of a frozen (-20 degrees C) solid sample, from a solution of dichloromethane- light petroleum. The two crystal forms display dissimilar patterns of hydrogen bonding and molecular assembly in the solid-state.

Chiral crystals from an achiral molecule: 4,6-di-O-benzyl-1,3-O-benzylidene-2-O-(4-methoxybenzyl)-myo-5-inosose - Gurale, Bharat P.; Gonnade, Rajesh G.; Shashidhar, Mysore S. (Acta Crystallographica Section C-Crystal Structure Communications, 2012)
The title achiral compound, C35H34O7, crystallizes in the chiral monoclinic space group P21. The molecules are densely packed to form a helical assembly along the crystallographic twofold screw axis via CH...O and CH...p interactions. Interestingly, the unit-translated helical chains are loosely connected via a rather uncommon edge-to-edge PhH...HPh short contact (H...H = 2.33 angstrom).

Elaboration of the ether cleaving ability and selectivity of the classical pearlman's catalyst [Pd(OH)(2)/C]: concise synthesis of a precursor for a myo-inositol pyrophosphate - Mart, Alson; Shashidhar, Mysore S. (Tetrahedron, 2012)
The cleavage of propargyl, allyl, benzyl, and PMB ethers by Pd(OH)(2)/C can be tuned in that order, by varying the reaction conditions. Other moieties such as C-C double bonds, esters, trityl ether, p-bromo and p-nitrobenzyl ethers are stable to these reaction conditions. Cleavage of allyl ethers can be made catalytic by using 1:1 mixture of Pd(OH)(2)/C and Pd/C. The synthetic potential of the selective ether cleaving ability of Pd(OH)(2)/C, essentially under neutral conditions, has been demonstrated by an efficient synthesis of a precursor for the preparation of an inositol pyrophosphate derivative. (C) 2012 Elsevier Ltd. All rights reserved.
Keywords: Cyclitol; Ether cleavage; Inositol; Palladium; Protecting group

Radical mediated deoxygenation of inositol benzylidene acetals: conformational analysis, DFT calculations, and mechanism - Gurale, Bharat P.; Vanka, Kumar; Shashidhar, Mysore S. (Carbohydrate Research, 2012)
Xanthates of 1,3-benzylidene acetal derivatives of myo- and neo-inositols undergo dideoxygenation under Barton-McCombie conditions, as a result of intramolecular abstraction of the benzylidene acetal hydrogen and subsequent cleavage of the acetal ring. Scrutiny of structure of these bicyclic inositol derivatives shows that although the conformation of the two rings can vary depending on the configuration of the inositol ring and the phase in which the molecules are present, both the xanthates lead to the formation of the same dideoxyinositol. DFT calculations on these molecular systems suggest that neo-inositol derivatives undergo conformational change prior to radical formation while myo- inositol derivatives undergo conformational change subsequent to radical formation, during the deoxygenation reaction. A low barrier for intramolecular hydrogen transfer supports the extreme facility of this deoxygenation reaction. (C) 2012 Elsevier Ltd. All rights reserved.
Keywords: Deoxygenation; DFT; Inositol; Mechanism; Radical; Xanthate

Solvent induced crystallization of 1,2,3,4(6),5-penta-O-acetyl-6(4)-O-[(1S)-10-camphor sulfonyl]-myo-inositol diastereomers associated via weak trifurcated C-H center dot center dot center dot O interactions - Manoj, Kochunnoonny; Gonnade, Rajesh G.; Shashidhar, Mysore S.; Bhadbhade, Mohan M. (CrystEngComm, 2012)
The title compound produced three different types of solvent inclusion crystals having a conserved dimeric association via trifurcated C-H center dot center dot center dot O interactions between the diastereomers. These `dimeric' units are organized differently to produce three crystal types containing guest molecules. In type I and II, unit translated dimers created voids for guest inclusion, whereas in type III the guest sites were produced by helical association of dimers. Inclusion of dichloromethane gave two different types of crystals; however, we were unable to obtain unsolvated crystals of the title compound.

Synthesis of the aminocyclitol units of (-)-hygromycin a and methoxyhygromycin from myo-inositol - Gurale, Bharat P.; Shashidhar, Mysore S.; Gonnade, Rajesh G. (Journal of Organic Chemistry, 2012)
Concise and efficient syntheses of the aminocyclitol cores of hygromycin A (HMA) and methoxyhygromycin (MHM) have been achieved starting from readily available myo-inositol. Reductive cleavage of myo-inositol orthoformate to the corresponding 1,3-acetal, stereospecific introduction of the amino group via the azide, and resolution of a racemic cyclitol derivative as its diastereomeric mandelate esters are the key steps in the synthesis. Synthesis of the aminocyclitol core of hygromycin A involved chromatography in half of the total number of steps, and the aminocyclitol core of methoxyhygromycin involved only one chromatography.

Identification of molecular crystals capable of undergoing an acyl-transfer reaction based on intermolecular interactions in the crystal lattice - Tamboli, Majid I.; Krishnaswamy, Shobhana; Gonnade, Rajesh G.; Shashidhar, Mysore S. (Chemistry-A European Journal, 2013)
Investigation of the intermolecular acyl-transfer reactivity in molecular crystals of myo-inositol orthoester derivatives and its correlation with crystal structures enabled us to identify the essential parameters to support efficient acyl-transfer reactions in crystals: 1)the favorable geometry of the nucleophile (OH) and the electrophile (CO) and 2)the molecular assembly, reinforced by CH interactions, which supports a domino-type reaction in crystals. These parameters were used to identify another reactive crystal through a data-mining study of the Cambridge Structural Database. A 2:1 co-crystal of 2,3-naphthalene diol and its di-p-methylbenzoate was selected as a potentially reactive crystal and its reactivity was tested by heating the co-crystals in the presence of solid sodium carbonate. A facile intermolecular p-toluoyl group transfer was observed as predicted. The successful identification of reactive crystals opens up a new method for the detection of molecular crystals capable of exhibiting acyl-transfer reactivity.
Keywords: Acylation; domino reactions; intermolecular interactions; solid-state reactions; X-ray diffraction

Orientation of the beta-hydroxyl group controls the diastereoselectivity during the hydride reduction and grignard reaction of inososes - Jagdhane, Rajendra C.; Patil, Madhuri T.; Krishnaswamy, Shobhana; Shashidhar, Mysore S. (Tetrahedron, 2013)
A comparison of the results of the Grignard reaction and the hydride reduction of the carbonyl group of epi- and scyllo-inososes reveals that the extent of diastereoselectivity of these reactions is decided by the orientation of the beta-hydroxyl group (or its derivative). Presence of an axial beta-hydroxyl group generally results in the formation of relatively larger amount of the axial alcohol as a result of the reduction of the carbonyl group. The possible reasons for the observed differences in diastereoselectivity between the reactions of these isomeric epi- and scyllo-inososes have been discussed. The sequence of reactions reported here provides convenient access to C-allcylated inositols, such as iso-laminitol and iso-mytilitol as well as 2-O-methyl epi-inositol, an epimer of the naturally occurring ononitol. (C) 2013 Elsevier Ltd. All rights reserved.
Keywords: Cyclitol; diastereoselectivity; Grignard; Inositol; Nucleophile; reduction

Acyl-transfer reactions in molecular crystals: reactivity correlation with crystal structure - Gonnade, Rajesh G.; Shashidhar, Mysore S. (Acta Crystallographica A‐Foundation and Advances, 2014)
Keywords: crystal engineering; intermolecular interactions; solid-state reactions

Correlation of the solid-state reactivities of racemic 2,4(6)-di-O-benzoyl-myo-inositol 1,3,5-orthoformate and its 4,4 `-bipyridine cocrystal with their crystal structures - Tamboli, Majid I.; Bahadur, Vir; Gonnade, Rajesh G.; Shashidhar, Mysore S. (Acta Crystallographica Section C-Structural Chemistry, 2014)
Racemic 2,4(6)-di-O-benzoyl-myo-inositol 1,3,5-orthoformate, C21H18O8, (1), shows a very efficient intermolecular benzoyl-group migration reaction in its crystals. However, the presence of 4,4 `-bipyridine molecules in its cocrystal, C21H18O8 center dot C10H8N2, (1)center dot BP, inhibits the intermolecular benzoyl-group transfer reaction. In (1), molecules are assembled around the crystallographic twofold screw axis (b axis) to form a helical self-assembly through conventional O-H center dot center dot center dot O hydrogen-bonding interactions. This helical association places the reactive C6-O-benzoyl group (electrophile, El) and the C4-hydroxy group (nucleophile, Nu) in proximity, with a preorganized El center dot center dot center dot Nu geometry favourable for the acyl transfer reaction. In the cocrystal (1)center dot BP, the dibenzoate and bipyridine molecules are arranged alternately through OH center dot center dot center dot N interactions. The presence of the bipyridine molecules perturbs the regular helical assembly of the dibenzoate molecules and thus restricts the solid-state reactivity. Hence, unlike the parent dibenzoate crystals, the cocrystals do not exhibit benzoyl-transfer reactions. This approach is useful for increasing the stability of small molecules in the crystalline state and could find application in the design of functional solids.
Keywords: acyl transfer; cocrystal; crystal structure; design of functional solids; helical assembly; hydrogen bonding; myo-inositol; solid-state reactions

Crystal-to-crystal thermal phase transformation of polymorphs of isomeric 2,3-naphthalene diol ditoluates: mechanism and implications for molecular crystal formation and melting - Tamboli, Majid I.; Krishnaswamy, Shobhana; Gonnade, Rajesh G.; Shashidhar, Mysore S. (Crystal Growth & Design, 2014)
Isomeric para- (1) and meta- (2) ditoluate derivatives of naphthalene 2,3-diol exhibited polymorphism producing three (Forms 1I, 1II, 1III) and two (Forms 2I, 2II) polymorphs each, respectively, depending on the solvent and conditions of crystallization. Crystal forms 1I, 1II, and 2I could be obtained repeatedly, whereas crystal forms 1III and 2II were obtained (separately) in one of the crystallization experiments, each. All the crystal forms were stable at ambient conditions, except for Form 2II, which disintegrated to a powder over 45 days. In contrast, the ortho-ditoluate (3) of naphthalene 2,3-diol did not exhibit polymorphism; it yielded fibrous chiral crystals from different solvents/conditions. Crystal structure analysis of all these polymorphs revealed dominance of energetically similar weak intermolecular interactions such as CH center dot center dot center dot O, CH center dot center dot center dot pi, pi center dot center dot center dot pi, and their interplay in molecular aggregation resulting in polymorphic modifications. Differential scanning calorimetry (DSC), hot stage microscopy, single crystal and powder X-ray diffraction measurements revealed crystal-to-crystal thermal transformation of Forms 1I and 1II crystals to Form 1III crystals and Form 2II crystals to Form 2I crystals. The transformation of Form 1I and Form 1II crystals to Form 1III crystals can be viewed as progressive destabilization of the crystal lattice during heating and converting to metastable phase, whereas the conversion of Form 2II to Form 2I crystals can be considered as reorganization of an unstable crystalline phase to a stable crystalline phase. Hence comparative studies of the structure of stable, metastable, or transient crystals and crystal-to-crystal transformations involving these forms could aid in unraveling the process of crystallization.

Myo-Inositol 1,3-acetals as early intermediates during the synthesis of cyclitol derivatives - Gurale, Bharat P.; Sardessai, Richa S.; Shashidhar, Mysore S. (Carbohydrate Research, 2014)
Synthetic sequences starting from commercially available myo-inositol necessarily involve protection-deprotection strategies of its six hydroxyl groups. Several strategies have been developed/attempted over the last several decades leading to the synthesis of naturally occurring phosphoinositols, their analogs, and cyclitol derivatives. Of late, myo-inositol 1,3-acetals, which can be obtained by the reductive cleavage of myo-inositol orthoesters have emerged as early intermediates for the synthesis of phosphorylated and other inositol derivatives. This mini-review is an attempt to illustrate the economy and convenience of using myo-inositol 1,3-acetals as early intermediates during syntheses from myo-inositol. (C) 2014 Elsevier Ltd. All rights reserved.
Keywords: Acetal; Cyclitol; Inositol; Protecting group; Signal transduction

Cocrystallization of 2,3-dihydroxynaphthalene with its para-, meta-, and ortho-ditoluates: insight into cocrystal formation and clues for the construction of supramolecular assemblies capable of intermolecular acyl group transfer reactivity - Tamboli, Majid I.; Bahadur, Vir; Gonnade, Rajesh G.; Shashidhar, Mysore S. (Crystal Growth & Design, 2015)
2,3-Dihydroxynaphthalene forms 2:1 cocrystals with its p-ditoluate and 1:1 cocrystals with its m-ditoluate but not with the o-ditoluate. In 2:1 cocrystals of the p-ditoluate, naphthalene diol molecules form a dimeric motif through OH...O hydrogen bonding interactions. The adjacent dimers sandwich the molecules of p-ditoluate through C-H...pi interactions. In 1:1 cocrystals of the m-ditoluate, naphthalene diol molecules generate a zigzag pattern through O-H...O hydrogen bonding interaction involving -OH of the diol and the C=O of the m-ditoluate. Intermolecular toluoyl group transfer reaction was more facile in cocrystals of the p-ditoluate as compared to cocrystals of the m-ditoluate. This difference in reactivity is consistent with the relative geometry of the electrophile (El, C-O) and the nucleophile (Nu, OH) in these cocrystals. A comparison of the cocrystallization behavior and structure of the two cocrystals with their constituents suggests that the position of the methyl group is crucial for cocrystal formation. A survey of the CSD revealed that the incidence of polymorphism and cocrystals formation decreases (number of hits) in the order para- > ortho- > meta- for disubstituted benzene derivatives. This suggests that compounds prone to exhibit polymorphism have more propensities to form cocrystals as compared to those that resist polymorphism. This information could be useful while selecting cocrystal formers and construction of supramolecular functional assemblies with desired properties.

Intramolecular cyclization of carbonate and thiocarbonate derivatives of myo-inositol in the solid state: implications for acyl group transfer reactions in molecular crystals - Tamboli, Majid I.; Shashidhar, Mysore S.; Gonnade, Rajesh G.; Krishnaswamy, Shobhana (Chemistry-A European Journal, 2015)
Racemic 4-O-phenoxycarbonyl and 4-O-phenoxythiocarbonyl derivatives of myo-inositol orthoformate undergo thermal intramolecular cyclization in the solid state to yield the corresponding 4,6-bridged carbonates and thiocarbonates, respectively. The thermal cyclization also occurs in the solution and molten states, but less efficiently, suggesting that these cyclization reactions are aided by molecular pre-organization, although not strictly topochemically controlled. Crystal structures of two carbonates and a thiocarbonate clearly revealed that the relative orientation of the electrophile and the nucleophile in the crystal lattice facilitates the intramolecular cyclization reaction and forbids the intermolecular reaction. The correlation observed between the chemical reactivity and the non-covalent interactions in the crystal of the reactants provides a way to estimate the chemical stability of analogous molecules in the solid state.
Keywords: crystal engineering; cyclitols; inositols; nucleophilic substitution; solid-phase synthesis

Engineering crystals that facilitate the acyl-transfer reaction: insight from a comparison of the crystal structures of myo-inositol-1,3,5-orthoformate-derived benzoates and carbonates - Tamboli, Majid I.; Krishanaswamy, Shobhana; Gonnade, Rajesh G.; Shashidhar, Mysore S. (ACTA Crystallographica Section C-Structural Chemistry, 2016)
Minor variations in the molecular structure of constituent molecules of reactive crystals often yield crystals with significantly different properties due to altered modes of molecular association in the solid state. Hence, these studies could provide a better understanding of the complex chemical processes occurring in the crystalline state. However, reactions that proceed efficiently in molecular crystals are only a small fraction of the reactions that are known to proceed (with comparable efficiency) in the solution state. Hence, for consistent progress in this area of research, investigation of newer reactive molecular crystals which support different kinds of reactions and their related systems is essential. The crystal structures and acyl-transfer reactivity of a myo-inositol-1,3,5-orthoformate-derived dibenzoate and its carbonate (4-O-benzoyl-2-O-phenoxycarbonyl-myo-inositol 1,3,5-orthoformate, C21H18O9) and thiocarbonate (4-O-benzoyl-2-O-phenoxythiocarbonyl-myo-inositol 1,3,5-orthoformate, C21H18O8S) analogs are compared with the aim of understanding the relationship between crystal structure and acyl-transfer reactivity. Insertion of an O atom in the acyl (or thioacyl) group of an ester gives the corresponding carbonate (or thiocarbonate). This seemingly minor change in molecular structure results in a considerable change in the packing of the molecules in the crystals of myoinositol-1,3,5-orthoformate-derived benzoates and the corresponding carbonates. These differences result in a lack of intermolecular acyl-transfer reactivity in crystals of myo-inositol-1,3,5-orthoformate-derived carbonates. Hence, this study illustrates the sensitivity of the relative orientation of molecules, their packing and ensuing changes in the reactivity of resulting crystals to minor changes in molecular structure.

Clues from crystal structures pave the way to access chiral myo-inositol derived versatile synthons: resolution of racemic 4-o-allyl-myo-inositol-1,3,5-orthoesters via corresponding dicamphanates by crystallization - Patil, Nivedita T.; Shashidhar, Mysore S.; Tamboli, Majid I.; Gonnade, Rajesh G. (Crystal Growth & Design, 2017)
Racemic 4-O-allyl-myo-inositol-1,3,5-orthoesters were resolved as the corresponding diastereomeric dicamphanates by crystallization from alcoholic solvents. Crystals of the two diastereomers of myo-inositol orthoacetate and one diastereomer each of myo-inositol orthoformate and myo-inositol orthobenzoate were obtained in >99% purity, on gram scale. The configuration of all these diastereomers was established by conversion to known chiral myo-inositol derivatives as well as by single crystal structure analysis. It is interesting to note that the procedures for the separation of diastereomeric myo-inositol orthoesters could be evolved due to the knowledge of crystal growth and crystal structures of inositol derivatives of comparable molecular structures. Due to the synthetic versatility of myo-inositol orthoesters, the methods described provide rapid and convenient access to a variety of chiral inositol derivatives with high synthetic potential.

Helical preorganization of molecules drives solid-state intermolecular acyl-transfer reactivity in crystals: structures and reactivity studies of solvates of racemic 2,6-Di-O-(4-fluorobenzoyl)-myo-inositol 1,3,5-orthoformate - Krishnaswamy, Shobhana; Shashidhar, Mysore S.; Bhadbhade, Mohan M. (Crystal Growth & Design, 2017)
Racemic 2,6-di-O-(4-fluorobenzoyl)-myo-inositol 1,3,5-orthoformate yielded structurally dissimilar solvent-free and solvated crystals depending upon the solvent of crystallization. The solvated crystals exhibited helical assembly of host molecules, due to the interaction of the guest molecules with the orthoformate moiety of the host. Some of the solvates showed specific but incomplete benzoyl group transfer reactivity below the phase transition temperature, whereas the reaction in solvent-free crystals led to a mixture of several products. These results reveal the necessity of helical molecular packing of the reacting molecules in their crystals to facilitate specific intermolecular acyl transfer reactivity. The crystal, structures of the fluorobenzoate solvates were similar to those of the solvates of the analogous chloro and bromobenzoates. The latter could be thermally :transformed into their solvent-free form via melt crystallization, resulting in the conversion of a helical molecular packing into a nonhelical molecular packing.

Correlation of intermolecular acyl transfer reactivity with noncovalent lattice interactions in molecular crystals: toward prediction of reactivity of organic molecules in the solid state - Krishnaswamy, Shobhana; Shashidhar, Mysore S. (Journal of Organic Chemistry, 2018)
Intermolecular acyl transfer reactivity in several molecular Acyl transfer reactivity can be predicted in solution based crystals was studied, and the outcome of the reactivity was analyzed in the light of structural information obtained from the crystals of the reactants. in solid state Minor changes in the molecular structure resulted in significant variations in the noncovalent interactions and packing of molecules in the crystal lattice, which drastically affected the facility of the intermolecular acyl transfer reactivity in these crystals. Analysis of the reactivity vs crystal structure data revealed dependence of the reactivity on electrophile ... nucleophile interactions and C-H center dot center dot center dot pi interactions between the reacting molecules. The presence of these noncovalent interactions augmented the acyl transfer reactivity, while their absence hindered the reactivity of the molecules in the crystal. The validity of these correlations allows the prediction of intermolecular acyl transfer reactivity in crystals and co-crystals of unknown reactivity. This crystal structure-reactivity correlation parallels the molecular structure-reactivity correlation in solution-state reactions, widely accepted as organic functional group transformations, and sets the stage for the development of a similar approach for reactions in the solid state.

Effect of crystal packing on the thermosalient effect of the pincer-type diester naphthalene-2,3-diyl-bis(4-fluorobenzoate): a new class II thermosalient solid - Tamboli, Majid I.; Karothu, Durga Prasad; Shashidhar, Mysore S.; Gonnade, Rajesh G.; Naumov, Pance (Chemistry-A European Journal, 2018)
The pincer-like double ester naphthalene-2,3-diyl-bis(4-fluorobenzoate) (2) is pentamorphic. Upon heating crystals of form I to below their melting point (441-443 K), they undergo a phase transition accompanied by a thermosalient effect, that is, rare and visually striking motility whereby the crystals jump or disintegrate. The phase transition and the thermosalient effect are reversible. Analysis of the crystal structure revealed that form I is a class II thermosalient solid. Crystals of form III also underwent a reversible phase transition in the temperature range of 160 to 170 K; however, they were not thermosalient. Comparison of the structures and the mechanical responses of the two polymorphs revealed that the thermosalient effect of form I was due to reversible closing and opening of the arms of the diester molecules in a tweezer-like action.

Inositol to aromatics -benzene free synthesis of poly oxygenated aromatics - Gurale, Bharat P.; Shashidhar, Mysore S.; Sardessai, Richa S.; Gonnade, Rajesh G. (Carbohydrate Research, 2018)
A method for the preparation of benzene derivatives from myo-inositol, an abundantly available phyto chemical is described. 1,3-Bridged acetals of inososes undergo step-wise elimination leading to the formation of polyoxygenated benzene derivatives. This aromatization reaction proceeds through the intermediacy of a beta-alkoxyenone, which could be isolated. This sequence of reactions starting from myoinositol, provides a novel route for the preparation of polyoxygenated benzene derivatives including polyoxygenated biphenyl. This scheme of synthesis demonstrates the potential of myo-inositol as a sustainable non-petrochemical resource for aromatic compounds. (C) 2018 Elsevier Ltd. All rights reserved.

Lithium hydride as an efficient reagent for the preparation of 1,2-anhydro inositols: does the reaction proceed through 'axial rich' conformation? - Sarkar, Nitai; Sardessai, Richa S.; Shashidhar, Mysore S.; Tamboli, Majid I.; Gonnade, Rajesh G. (Carbohydrate Research, 2018)
scyllo-Inositol derived 1,2-trans-diequatorial halohydrins can be efficiently converted to the corresponding epoxides in the presence of lithium hydride. The structure of one of the epoxides was determined by single crystal X-ray diffraction analysis. This provides a potential route for the preparation of ring modified inositol derivatives. DFT calculations suggest that this epoxide formation could be proceeding through the intermediacy of the cyclohexane ring-inverted axial-rich conformer (1,2-trans-diaxial halohydrin). This is supported by the results of DFT calculations on the formation of inositol orthoformate, where the product is locked in the axial-rich conformation, while the starting inositol has the equatorial-rich conformation.

Cocrystallization of 2,3-dihydroxynaphthalene with its para-, meta-, and ortho-ditoluates: insight into cocrystal formation and clues for the construction of supramolecular assemblies capable of intermolecular acyl group transfer reactivity (vol 15, pg 12 - Tamboli, Majid I.; Bahadur, Vir; Gonnade, Rajesh G.; Shashidhar, Mysore S. (Crystal Growth & Design, 2019)

Intermolecular acyl-transfer reactions in molecular crystals - Shashidhar, Mysore S.; Krishnaswamy, Shobhana (Accounts of Chemical Research, 2019)
CONSPECTUS: It is far more difficult to recognize and predict the chemical reactions that a molecule of an organic compound can undergo in crystalline (solid) state as compared to the solution state (the "organic functional group" approach), since the published data on solid-state structure reactivity investigations and correlations are scant. The discovery of the first intermolecular acyl-transfer reaction in molecular crystals of racemic 2,4-di-O-benzoyl-myo-inositol-1,3,5-orthoformate (DiBz) during our attempts to develop methods for the synthesis of phosphoinositols, motivated us to find other molecular crystals capable of supporting similar reactions. Small changes to the molecular structure of DiBz yielded analogues with different crystal structures which showed varying degrees of acyl transfer reactivity as compared to the crystals of DiBz. A systematic investigation of the structures, polymorphism, cocrystallization behavior, and the corresponding reactivity of these crystals allowed us to correlate the acyl transfer reactivity with their structures and inherent noncovalent interactions and provided crucial insights into the mechanism of these reactions. Polymorphs or cocrystals of these compounds exhibited dissimilar reactivities due to differences in the molecular conformation and/or arrangements in their crystals. The knowledge of phase transitions between polymorphs enabled us to control and tune the reactivity in the solid state. We could identify three conditions essential for intermolecular acyl transfer: (i) favorable relative geometry of the electrophile (ester C=O) and the nucleophile (OH), (ii) noncovalent interactions (C-H center dot center dot center dot pi) between the reacting molecules which help in maintaining the facility and specificity of the reaction, and (iii) the presence of channels in the lattice which enable propagation of the reaction in the crystal. Based on this supramolecular structure reactivity correlation, we identified other molecular crystals (composed of molecules of widely different molecular structure from that of DiBz) from a survey of the Cambridge Structural Database (CSD) and predicted their acyl transfer reactivity. The increased availability of user-friendly modern X-ray diffractometers and related software has enabled efficient collection, analysis and interpretation of single crystal X-ray diffraction data, essential for such studies. The rapidly expanding CSD facilitates the identification of crystals with similar structures and reactivity patterns. In a wider perspective, facile reactions in molecular crystals fascinate chemists because these reactions usually exhibit unique product selectivity and have the potential to be developed as sustainable green reactions. We are optimistic that similar approaches for the study of other group transfer reactions in molecular crystals would augment and widen the scope of chemical reactions in molecular crystals in particular and the solid state in general. The ability to predict the reactivity of molecules in their crystals could find applications in organic synthesis, material science and industry. Realization of the involvement of inositol derivatives in cellular processes led to the discovery of cellular signal transduction mechanisms. The ability of inositol derivatives to support facile acyl-transfer reactions in the crystalline state might well have opened a new avenue for research in the area of organic solid-state reactions.

Access to enantiomeric organic compounds with potential for synthesis via racemic conglomerates: inositol derivatives as a case in point - Patil, Nivedita T.; Patil, Madhuri T.; Sarkar, Nitai; Gonnade, Rajesh G.; Shashidhar, Mysore S. (Crystal Growth & Design, 2021)
The crystal structure database was used to identify inositol derivatives that could be crystallizing as racemic conglomerates. Among the six racemic inositol derivatives identified, racemic 4-O-tosyl-6-O-benzyl-myo-inositol-1,3,5-orthoformate (A) was found to be a true conglomerate and was resolved on the multigram scale by the preferential crystallization technique. This resolution procedure does not require the use of any enantiomeric resolving agent. The resolved enantiomers of A are useful for the synthesis of natural and unnatural enantiomeric derivatives of inositol, since they carry orthogonal hydroxy protecting groups. Racemic 4-O-methanesulfonyl-myo-inositol-1,3,5-orthoformate (B) on crystallization from common organic solvents generally yielded racemic twin crystals, while in the presence of structural analogs as additives, they yielded true racemic crystals. A comparison of the crystal structures of the true racemate, twinned crystal and crystal of one of the enantiomers of B, revealed the reasons for the formation of polymorphic (twin) crystals. Such instances are relatively rarely encountered but nevertheless shed light on our understanding of polymorphism and twinning of crystals.

Construction of two-component chemically reactive supramolecular assemblies-acyl migration reactions in cocrystals of napthalene-2,3-diol and its diesters - Bahadur, Vir; Gonnade, Rajesh G.; Tamboli, I. Majid; Krishnaswamy, Shobhana; Shashidhar, Mysore S. (ChemPlusChem, 2021)
Reactions in solids are of contemporary interest due to applications in pharmaceutical industries to environmental sustainability. Although several reactive crystals that support chemical reactions have been identified and characterized, the same cannot be said about reactive cocrystals. Earlier we correlated the facile acyl group transfer reactions in crystals with supramolecular parameters obtained from the crystal structures. The structure-reactivity correlation revealed the requirement of proper juxtaposition of electrophile (C=O) and the nucleophile (OH) with distance (similar to 3.2 angstrom) and angle (similar to 90 degrees) along the chain structure. The current article describes the preparation of cocrystals that are capable of supporting intermolecular acyl group transfer reactions in a group of structurally similar molecules. The cocrystals of naphthalene 2,3-diol and its corresponding diesters showed a facile solid state acyl transfer reaction, which has been well correlated with their crystal structures.
Keywords: Acylation; domino reactions; intermolecular interactions; reaction in cocrystal; solid-state reactions; X-ray diffraction

Palladium mediated selective cleavage of benzyl and allyl phosphates: a convenient non-hydrogenolytic method for the synthesis of phosphates and phospholipids. - Mart, Alson; Sarkar, Nitai N.; Shashidhar, Mysore S. (ChemistrySelect, 2022)
Palladium(II) hydroxide on carbon is a catalyst routinely used for the cleavage of O-benzyl groups by hydrogenolysis to obtain the corresponding parent organic compound. The work described in this article shows that allyl and benzyl phosphates, can be cleaved efficiently and selectively using palladium(II) hydroxide on carbon, under non-hydrogenolytic and neutral conditions, precluding the migration of acyl groups. The utility of these cleavage reactions for the synthesis of diacylglycerol and phosphatidic acid, containing unsaturation, is demonstrated. These methods have high potential for the synthesis of a variety of phosphates and natural phospholipids.
Keywords: Carbohydrate; Ether cleavage; Palladium; Phosphate; Phospholipid; Protecting group

Desymmetrization of myo-inositol - Patil, Nivedita T.; Patil, Madhuri T.; Gonnade, Rajesh G.; Shashidhar, Mysore S. (Carbohydrate Research, 2025)
Chemistry and biology of phosphoinositols have been intensely investigated areas of research over the last 4-5 decades due to their involvement in cellular signal transduction pathways. Efficient laboratory synthesis of enantiomeric derivatives of inositols was a central issue since they were required for the delineation of the myo-inositol cycle as well as for the total synthesis of polyol based natural products and their derivatives. This essentially meant the development of competent methods for the desymmetrization of myo-inositol leading to the preparation of enantiomeric O-substituted derivatives of myo-inositol. This was approached by: the classical resolution methods involving separable diastereomers, the chiral pool synthesis, enzyme catalysis, asymmetric catalysis and preferential crystallization of enantiomers in a racemic conglomerate. This review summarizes results obtained in author's laboratory, as well as those reported in the literature on attempts at desymmetrization of myo-inositol.
Keywords: Conglomerate; Crystallization; Cyclitol; Enantiomers; Inositol; Lipid